Comparison of Performance and Emission Characteristics of Biofuel and Diesel Fired Engine - P, Dinesha; K, Prof. (Dr) Jagannath (Distributed Generation & Alternative Energy Journal, 2018)
Biodiesel is playing an important role in transport sector as a substitute for petroleum fuels. The present study diagnoses the use of phenolic biofuel blends namely, cardanol at higher fuel injection pressure on the performance and exhaust emissions of a direct injection, 4-stroke, single cylinder compression ignition engine. In this study, biofuel blends used with three different percentage composition of cardanol such as B10M10, B20M10 and B30M10. The results are compared with base line diesel operation at 180 bar standard injection pressure. The experimental results show better engine performance and exhaust emission characteristics for the biofuel blends at 220 bar injection pressure. Biofuel blend B20M10 gives better performance and emission results when compared to B30M10, and there is not much difference in the results when compared to B10M10. B20M10 blend gives slightly lower brake thermal efficiency (BTE), sharp reduction in carbon monoxide (CO), unburnt hydrocarbon (HC) and smoke emissions and drastic increase in oxides of nitrogen emissions (NOx), when compared to baseline diesel operation.